2004
DOI: 10.1902/jop.2004.75.2.236
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐Effect Relation of Smoking and the Interleukin‐1 Gene Polymorphism in Periodontal Disease

Abstract: There is a gene-environmental interaction between smoking and the IL-1 genetic polymorphism. Smokers bearing the genotype-positive IL-1 allele combination have an increased risk of periodontitis. The IL-1 genotype has no influence in non-smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 35 publications
(45 reference statements)
2
55
1
2
Order By: Relevance
“…It should also be considered that a gene-environmental interaction between smoking and the IL-1 genetic polymorphism has been recently reported: PAG-positive smokers had an enhanced smoking-associated periodontitis risk as compared to their IL-1 genotype-negative counterparts. 46 However, in GAP, Hodge et al 38 failed to detect an association with IL-1 genotypes and smoking status which, when included in the analysis as a covariate, did not influence the results.…”
Section: Discussionmentioning
confidence: 96%
“…It should also be considered that a gene-environmental interaction between smoking and the IL-1 genetic polymorphism has been recently reported: PAG-positive smokers had an enhanced smoking-associated periodontitis risk as compared to their IL-1 genotype-negative counterparts. 46 However, in GAP, Hodge et al 38 failed to detect an association with IL-1 genotypes and smoking status which, when included in the analysis as a covariate, did not influence the results.…”
Section: Discussionmentioning
confidence: 96%
“…Kornman et al (17) found a significantly higher prevalence of positive genotypes in non-smokers with severe PD, and Shirodaria et al (35) reported a significant association between the IL-1A polymorphism (+4845) and a higher risk of severe PD in non-smokers. However, findings of studies from 3 consecutive years (20,36,37) showed that only smokers with positive IL-1 genotype were at a higher risk of PD, concluding that tobacco use is a more important risk factor than genetics. Drozdzik et al (38) found no significant association between the presence of the IL-1B polymorphism (+3953) and the periodontal status of patients, consistent with the present study, describing plaque index and age as more influential risk factors.…”
Section: Discussionmentioning
confidence: 98%
“…However, other authors found no such correlation (18)(19)(20), thus the issue remains controversial. The aim of the present study was to examine the association between IL-1β in GCF and PD activity and to investigate the presence of IL-1 gene polymorphisms and their possible relationship with the disease, in a Spanish population.…”
Section: Introductionmentioning
confidence: 92%
“…Several studies reported relationships between IL-1-positive genotypes and smoking; however, other studies demonstrated that the association of IL-1-positive genotypes with the severity of periodontal disease was independent of smoking, suggesting no relationship between smoking and IL-1 genotypes. Logistic regression analysis revealed that odds ratios of periodontal disease, in comparison with IL-1 genotype-negative non-smokers as a reference group, was 0.98 for genotype-positive non-smokers, 2.37 for genotype-negative smokers, and 4.50 for genotype-positive smokers, suggesting synergism between IL-1 polymorphism and smoking (Meisel et al, 2004). An association between IL-6 and IL-10 genotype and periodontal status was more conspicuous in non-smokers.…”
Section: Gene-smoking Relationshipmentioning
confidence: 96%